Rancang Bangun Sistem Informasi Penjualan Tanaman Hias dengan Pendekatan Teknologi Berbasis Web di JA Garden - Sarulsetia, Bagus (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2025)
The rapid development of information technology has provided opportunities for various sectors to improve operational efficiency and effectiveness, including in the field of ornamental plant sales. This study aims to design and implement a web-based Ornamental Plant Sales Information System at JA Garden to overcome the constraints of manual systems that often cause delays, errors, and lack of efficiency in managing sales data. This system is designed using various web-based programming languages, such as HTML, CSS, jQuery, JavaScript, JSON, and PHP, with database processing based on Structured Query Language (SQLi). The supporting software used includes XAMPP version 5.6, Notepad++, and the Google Chrome browser. The results of this study indicate that the designed information system is able to produce accurate sales data, speed up the transaction process, and facilitate the delivery of information to customers and management. In addition, this system also reduces the level of errors in data management, which previously often occurred in manual systems. With this system, JA Garden can optimize its business processes, increase customer satisfaction, and strengthen competitiveness in the digital era. As a suggestion, the management of this system requires competent workers (brainware) to ensure that the system is used optimally and supports sustainable business development.